On Answer to Kirk-Shahzad’s Question for Strong b-TVS Cone Metric Spaces - Hieu, Doan Trong; Hung, Bui The; Sirajo Abdullahi, Muhammad; Kumam, Poom (Science & Technology Asia, 2022)
In this paper, we introduced the concept of strong b-TVS cone metric space. Furthermore, we proved that any strong b-TVS cone metric space has a completion. Our results gave an analogue answer to Kirk-Shahzad’s question in the case of strong b-TVS cone metric spaces.